PHAGE-ASSOCIATED LYTIC ENZYMES FOR TREATMENT OF BACILLUS ANTHRACIS AND RELATED CONDITIONS (2008)
Bacillus anthracis B. cereus Bacillus anthracis Bacillus anthracis The present disclosure relates to methods, compositions and articles of manufacture useful for the treatment of and bacteria and spores, and related conditions. The disclosure further relates to methods and compositions for the identification of a phage associated lytic enzyme to rapidly and specifically detect and kill and other bacteria. Related articles of manufacture, methods of degrading spores and methods of treatment of infections or bacteria populations of, or subjects exposed to or at risk for exposure to, are also provided.